The Implementation Of A Fraud Risk Assessment In The Disbursement Of Government Assistance At The ABC Government Institution - Rizal Shobirin; Lufti Julian (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The potential for fraud in distributing government assistance, particularly operational assistance, remains relatively high. The ABC Government Institution is one of the institutions responsible for distributing such assistance. Therefore, concrete efforts are needed to prevent fraud in the distribution process. This study aims to apply a Fraud Risk Assessment (FRA) to identify potential fraud risk scenarios that may occur in the distribution of government assistance by the ABC Government Institution. A qualitative research approach with a case study method was used in this study. Based on the FRA results, seven fraud risk scenarios were identified that the organization needs to address. These include two scenarios classified as very high risk, one as medium risk, three as low risk, and one as very low risk, evaluated by the organization's risk appetite.